KEDUDUKAN DAN WEWENANG MAHKAMAH KONSTITUSI DALAM SISTEM HUKUM KETATANEGARAAN INDONESIA - Nanang Sri Darmadi (Jurnal Hukum, 2012)
Fundamental changes in the 1945 is the amendment of Article 1 paragraph (2) as follows: "Sovereignty belongs to the people and carried out according to the Constitution". Change the 1945 Constitution has given rise to the Constitutional Court. By the Constitutional Court, the constitution guaranteed as the supreme law that can be enforced as it should. The Constitutional Court in its development, it is feared will be the agency that has authority super body.Particularly in resolving the matter related to its authority, the Constitutional Court can unilaterally interpret the Constitution without being questioned, other than that produced the Constitutional Court ruling is final and binding, so that when there is one party who feels aggrieved by the decision of the Constitutional Court cannot make the effort for other law.From the approach used in this study is normative juridical, because the study was conducted by examining library materials or secondary data relating to the status and authority of the Constitutional Court in constitutional legal system of Indonesia. Specifications of this research is descriptive analysis, which is expected to give a detailed overview, systematic, and comprehensive on all matters relating to the object to be examined. The data used in this study is secondary data, it means the data obtained from library materials collected through the study of literature and documentary studies, which are then analyzed qualitatively. The conclusion of this study is that the formation of the Constitutional Court in Indonesia is inseparable from the development of judicial review occurring in several countries in the world, especially during the implementation of judicial review which was pioneered by John Marshall in Marbury versus Madison case.Thinking about the importance of the Constitutional Court in Indonesia has emerged during the discussion of the draft Constitution in BPUPKI, then the idea of judicial review of the need to re-emerge during the discussion draft Judicial Power Act (Act No. 14 of 1970). At the time of the discussion of the 1945 changes in the era reformation, the opinion of the importance of the Constitutional Court appeared. Ultimately, the Third Amendment to the 1945 to be of the Constitutional Court, which serves as the guardian of the Constitution and constitutional interpretation.